Determinan niat beli ulang dengan kepuasan elektronik sebagai variabel mediasi pada pengisian saldo di perdagangan daring - Calvin Jordan Wijaya Affendi; Keni Keni (Universitas Kristen Maranatha, 2025)
This study aims to determine the effect of website design quality, e-trust, price fairness, and e-satisfaction on repurchase intention in the e-commerce industry in the top-up service. Data collection was conducted online by using Google Form with the sample selection technique being convenience sampling. The number of respondents were 169, but 19 respondents didn’t meet the sample’s criteria, thereby this study only analyzed the data from 150 respondents who have made purchases in an e-commerce that offers top-up services more than twice in the past year. Moreover, the data were analyzed by using PLS-SEM method through SmartPLS software. Based on the results of data analysis, price fairness and e-satisfaction have a positive and significant influence on repurchase intention. Moreover, website design quality and e-trust have a positive and significant influence on e-satisfaction, while website design quality and e-trust have a positive and significant influence on repurchase intention when mediated by e-satisfaction. However, website design quality and e-trust don’t have any significant influence on repurchase intention. The results suggest that e-commerce, who offer top-up services, needs to focus on improving customer satisfaction, which will motivate customers to make repeated purchases. Moreover, the e-commerce needs to consistently consider the price fairness perceived by customers by observing the comparison of the product’s value and its price, as well as the competitor’s price for a similar value. The results of this study are expected to be considered by e-commerce to determine the appropriate marketing strategy to improve the customer’s intention to make repeated purchases.